2010
DOI: 10.1021/ie1012807
|View full text |Cite
|
Sign up to set email alerts
|

Revisit of the Wall Effect on the Settling of Cylindrical Particles in the Inertial Regime

Abstract: The wall effect on the settling of cylindrical particles in the inertial regime is revisited. This study covers particle Reynolds number from 600-16100 and particle length-to-diameter ratio (l/d) from 4-21. The wall factor (U t /U t,∞ ) is found to decrease initially as the particle-tocolumn diameter ratio (d/D) increases. When wall effect becomes significant, U t /U t,∞ starts to increase with an increase in d/D due to a change of the particle orientation during settling. After U t /U t,∞ reaches a maximum, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…that drag increases as shape becomes less spherical, especially for particles with high aspect ratio [23,26,59] and thus expected drag coefficients for ZM and ZMCA would be higher than for the spheroidal CPM, suggesting the Stokes equation may over estimate their respective settling velocities. For ZMCA in particular, drag may be significantly increased, especially if particles orientate towards a flat conformation of maximum drag resistance upon settling [11,27,28].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…that drag increases as shape becomes less spherical, especially for particles with high aspect ratio [23,26,59] and thus expected drag coefficients for ZM and ZMCA would be higher than for the spheroidal CPM, suggesting the Stokes equation may over estimate their respective settling velocities. For ZMCA in particular, drag may be significantly increased, especially if particles orientate towards a flat conformation of maximum drag resistance upon settling [11,27,28].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The role of particle shape on hindered settling exponents has been a focus of previous studies, where evidence would suggest that values increase as the particles become less spherical [22][23][24][25][26] due to the enhanced drag. For particles with large aspect ratio, orientation may also be an important factor, where research has shown that rod-like particles in particular may naturally orientate towards a flat conformation of maximum resistance upon settling [11,23,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches include those analysing the transmission-attenuation response of laser light in sample based devices such as the Lumizier (from Lum GmbH) and Turbiscan (Formulation, SA) [9][10][11]; however, these ex situ systems are only suitable for small sample analysis of slowly evolving suspensions. In situ devises include light based transmission/backscatter or fluorescence devices [12][13][14][15][16][17][18], CCD video analysis [19][20][21][22][23], gamma ray [24,25] or x-ray CATSCAN [26], and also tomographic techniques which measure electrical resistance within suspensions [27,28]. However, a number of these techniques suffer from common limitations to their use, such complicated set-ups that encompass specific vessel requirements (and hence are not suitable for deployment industrially) while many are highly intrusive, or complex and expensive in application [29].…”
Section: Introductionmentioning
confidence: 99%
“…for CPA) should be 50 particle diameters above the bottom to account for a friction error of less than 0.6 % (Allen, 1999). As shown recently, cylindrical particles may orient with regard to the wall and settle in narrow cylindrical cells even faster (Lau et al, 2010).…”
Section: Fig 13mentioning
confidence: 66%